Prediction of emotional disorder in workers from organizational support and workplace bullying (Research, Society and Development, 2021)
The changes that have occurred in the world of work in recent years have required organizations and workers to modify their strategies of action aiming at greater efficiency and productivity with less working illness. In this context, management has encouraged their talents to reinvent themselves, a condition which may intensify pressures on the workplace pace and responsibilities, by making work processes precarious and putting workers' health at risk, especially with regard to mental disorder. Thus, such demands, whether subtle or not, conscious or not, may be inserted in a process of humiliation and in the creation of a low bond between the worker and the organization. In this way, the present article aims to assess how much organizational support and bullying would influence mild mental disorder in the workplace.  A number of 212 workers at ages varying from 20 to 67 participated in the study, most of them from the private sector, women, with married marital status and having an average of 9.19 years of service. The data analysis, referring to descriptive analysis performed in SPSSWIN in its version 24.0, were: Cronbach's alpha, linear regression and ANOVA. It was observed that the scales used presented reliable psychometric indicators for the referred sample and that the hypothesis related to organizational support, bullying at work and predictors of emotional disorder were confirmed, as well as, in the ANOVA calculation, those who presented scores in the low organizational support and higher scores in bullying are likely to present higher-order emotional disorders (anxiety, depression and stress). Based on these results, an organizational dynamic that has less support and/or leads the employee to a low employment relationship may contribute to moral harassment, which will influence the emergence of the emotional disorder.